2022
DOI: 10.1210/clinem/dgac240
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Identification of a Novel, Externally Validated Predictive Test for Gestational Diabetes Mellitus

Abstract: Context Undiagnosed gestational diabetes (GDM) is a major preventable cause of stillbirth. In the UK, women are selected for diagnostic testing for GDM based on risk factors, including BMI >30kg/m 2. Objective To improve the prediction of GDM using metabolomics. Methods We performed metabolomics on maternal serum from the Pregnancy Outcome Prediction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Given that SEP and NMR metabolic traits can inform on adverse pregnancy and perinatal outcomes [4][5][6][7][8][9] , our findings suggest SEP might influence adverse pregnancy and perinatal outcomes via effects on metabolic traits.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Given that SEP and NMR metabolic traits can inform on adverse pregnancy and perinatal outcomes [4][5][6][7][8][9] , our findings suggest SEP might influence adverse pregnancy and perinatal outcomes via effects on metabolic traits.…”
Section: Discussionmentioning
confidence: 80%
“…We found that lower SEP associated with higher levels of the inflammatory marker glycoprotein acetyls corroborates findings from a study of 605 women showing that higher educational level was associated with lower inflammatory biomarkers in pregnancy 27 . Given that SEP and NMR metabolic traits can inform on adverse pregnancy and perinatal outcomes 49 , our findings suggest SEP might influence adverse pregnancy and perinatal outcomes via effects on metabolic traits.…”
Section: Discussionmentioning
confidence: 84%
“…This limitation in diversity may limit the external validity of the findings. However, previous POP study findings have been successfully validated in the Born in Bradford (BiB) study, whose population is significantly more diverse 11,35,36 . For the present study, external validation using the BiB study samples was not performed because of the unavailability of some of the metabolites included in the models developed in the POP study (https://osf.io/axqsu, accessed 11 September 2023).…”
Section: Discussionmentioning
confidence: 99%
“…7 Metabolomics has shown potential to contribute to the improved prediction of various pathologies of pregnancy, such as pre-eclampsia, fetal growth restriction and gestational diabetes mellitus. [8][9][10][11][12] In addition, several studies have been published on the metabolomic prediction of sPTB or time to spontaneous labor. [12][13][14][15][16][17][18][19][20][21][22][23][24] However, metabolomics analyses involve complex data sets, with a vast number of predictors and relatively small sample sizes, known as the 'large p, small n problem'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation